Peran Mahasiswa Kuliah Kerja Nyata Memberdayakan Masyarakat Dalam Meningkatkan Perekonomian Desa Sindangsari - Cecep Hidayat; Dian Budhi Santoso (Peneliti.net, 2023)
The Integrative Thematic Real Work Lecture (KKN) at Singaperbangsa Karawang University with the title Optimizing Community Empowerment in Development to Improve the Economy of Sindangsari Village, Kutawaluya District, Karawang Regency, consisting of 23 students with various study programs. The Integrative Thematic Community Service Team carries out various work programs offline with due observance of health protocols during the period August – September 2022. As a concrete form of the university's contribution to society, industry, local government and community groups who want to be economically and socially independent, the Integrative Thematic Community Service team is actively observing and extracting data to find out existing problems, find solutions and create increased community empowerment.